Assessment of Iron Status in Iraqi Females at Reproductive Age Affected with Celiac Disease - Kamal, Farah; Kadhim, Nada A. (Iraqi Journal of Science, 2024)
Celiac disease (CD) is a serious autoimmune disease that occurs in people who eat gluten, leading to damage to the small intestine and nutrients that cannot be properly absorbed into the body. The study population consists of 140 female participants, 100 of whom have CD at reproductive age and are matched with apparently healthy females of the same age. The study was carried out in the Chemistry Department at the University of Baghdad and Baghdad Educational Hospital (Baghdad, Iraq). The present study aimed to evaluate the effect of CD on iron indices in females who have anemia and others who do not. Iron, unsaturated iron-binding capacity (UIBC), Total iron binding capacity (TIBC), ferritin, transferrin, and Complete blood count (CBC) were measured. According to the study findings, 28(28%) of the female patients had Hb equal to or greater than 12, while 72(72%) of them had Hb less than 12. Hematological indices also revealed numerous significant differences (P<0.05) between the patient and control groups. The iron indicators of the patients were measured and revealed significant variations that indicated the presence of iron deficiency anemia. Iron, ferritin, and Transferrin were decreased in patients compared to the control group, while TIBC, UIBC, and transferrin were increased. This study demonstrated that the majority of newly diagnosed female CD participants had Hb levels less than 12, as well as low iron and ferritin levels. Hematological indices also indicated iron deficiency anemia.